Lelangan sebagai Sistem Perekonomian Tradisional di Desa Julah - Nitiprabhu Pramatatya; Bambang Dharwiyanto Putro; I Nyoman Suarsana (Department of Anthropology Udayana University, 2019)
Julah village is an old village called Bali Mula village or Bali beginings, it is located in Tejakula District, Buleleng Regency, Julah village has a traditional economic system called lelangan or traditional auction market, the auction market is managed and maintained by the Julah Traditional Organization, especially as a valuable asset which is the main income for customary cash. To examine this problem, there are certain formulation used in this research, namely : 1) What are the characteristics of the traditional auction market in Julah village? 2) Why does the traditional auction market stll exist in Julah village? 3) What are the implications of the existence of a traditional auction market on social life in Julah village? The types of data used in this study are qualitative data and quantitave data as a secondary data sources obtained through observation, interviews, literature study and documents, the analysis used is descriptive analysis. This research uses Functionalism theory from Bronislaw Malinowski, Hierarcy of Needs theory from Abraham Maslow and theory of Personalitic Economics from Dewey and Szanton. The concepts in this research are existence, traditional auction market and modernization. The existence of the lelangan in the middle of the modernization era is due to cultural conservation carried out by the Julah Community and Customary Organization itself, the utilization of Julah’s natural resources in the form of village abian land or village – owned gardens whose garden products are auctioned off as a source of income for adat, besides that the community also has socio – economic function and functions of the arena of social interaction for the Julah Cummunity